Thiol-yne click chemistry: A powerful and versatile methodology for materials synthesis - Lowe, Andrew; Hoyle, C.; Bowman, C. (The Royal Society of Chemistry, 2010)
Radical mediated thiol-yne polymerization reactions complement the more well-known thiol-ene radical polymerization processes, with the added advantage of increased functionality. In one system studied, the rate constant for the addition of the thiol to the vinyl sulfide created by the initial reaction of the thiol with the alkyne is three times faster than the initial reaction. When hydrocarbon based dialkynes and dithiols were copolymerized, the resulting thiol-alkyne networks containing only hydrocarbon and sulfide linking groups exhibited refractive index values tunable above 1.65, with the refractive index directly related to the sulfur content. The thiol-yne reaction was also found to be useful in functionalizing thiol-terminated polymer chain ends via sequential Michael thiol-ene addition followed by the thiol-yne reaction: the result is the dual functionalization of the polymer chain end. A thermally responsive polymer hydrogel network was formed when an yne terminated water-soluble homopolymer was polymerized with a tetrafunctional thiol. © The Royal Society of Chemistry 2010.